Global value chains and wages: international evidence from linked worker-industry data - Parteka, Aleksandra; Wolszczak-Derlacz, Joanna (Luxembourg, 2016)
"Using a rich dataset on over 110,000 workers from nine European countries and the USA we study the wage response to industry dependence on foreign value added. We estimate a Mincerian wage model augmented with an input-output interindustry linkages measure accounting for task heterogeneity across workers. Low and mediumeducated workers and those performing routine tasks experience (little) wage decline due to major dependency of their industries on foreign inputs. Workers from former EU15 are more in danger of unfavourable wage effects than workers from new EU member states. American workers employed in service industries are more exposed than manufacturing workers."